Learning higher-order thinking skills using problem-based learning model - Tama, N S; Aisyah, N; Santoso, B; Kurniadi, E (Journal of physics. Conference series, 2020)
This research is a descriptive qualitative research to describe student activities during learning by applying Problem-based learning model and students' higher-order thinking skills after applying higher-order thinking skills based learning using problem based learning (PBL) model on the two-variable linear equation system topic. The study was conducted at a Junior High School in Palembang, with research subjects totaling six students in class VIII3. The learning process was adjusted to the phases of the Problem-based learning model. The researcher uses higher-order thinking skills questions on students' worksheets and test questions. Data collection techniques in this study used observation sheets, test results, and interview results. The results of this study indicate that the dominant student activity arises is discussing with the group in planning problem solving strategies, listening to exemples of problems given and solving problems that exist on the student worksheets using problem solving strategies that have been discussed as well as dominant higher-order thinking skills emerge is analytical skills.